Effort-Reward Imbalance at Work and Incident Coronary Heart Disease: A Multicohort Study of 90,164 Individuals - Dragano, Nico; Siegrist, Johannes; Nyberg, Solja T; Lunau, Thorsten; Fransson, Eleonor I; Alfredsson, Lars; Bjorner, Jakob B; Borritz, Marianne; Burr, Hermann; Erbel, Raimund; Fahlén, Göran; Goldberg, Marcel; et al. (Epidemiology (Cambridge, Mass.), 2017)
Epidemiologic evidence for work stress as a risk factor for coronary heart disease is mostly based on a single measure of stressful work known as job strain, a combination of high demands and low job control. We examined whether a complementary stress measure that assesses an imbalance between efforts spent at work and rewards received predicted coronary heart disease. This multicohort study (the "IPD-Work" consortium) was based on harmonized individual-level data from 11 European prospective cohort studies. Stressful work in 90,164 men and women without coronary heart disease at baseline was assessed by validated effort-reward imbalance and job strain questionnaires. We defined incident coronary heart disease as the first nonfatal myocardial infarction or coronary death. Study-specific estimates were pooled by random effects meta-analysis. At baseline, 31.7% of study members reported effort-reward imbalance at work and 15.9% reported job strain. During a mean follow-up of 9.8 years, 1,078 coronary events were recorded. After adjustment for potential confounders, a hazard ratio of 1.16 (95% confidence interval, 1.00-1.35) was observed for effort-reward imbalance compared with no imbalance. The hazard ratio was 1.16 (1.01-1.34) for having either effort-reward imbalance or job strain and 1.41 (1.12-1.76) for having both these stressors compared to having neither effort-reward imbalance nor job strain. Individuals with effort-reward imbalance at work have an increased risk of coronary heart disease, and this appears to be independent of job strain experienced. These findings support expanding focus beyond just job strain in future research on work stress.